Using Participatory Theater And Arts For Youth Empowerment And Conflict Resolution In Post-Conflict Communities - Mary Apisai; Lenny Waga; Daniel Kele (Yayasan Adra Karima Hubbi, 2026)
Post-conflict communities often struggle with persistent trauma, weakened social cohesion, and limited youth agency in rebuilding peace. Young people, who are frequently among the most affected by violence, face ongoing psychosocial challenges and social exclusion, making their empowerment critical to sustainable conflict recovery. Participatory theater and arts have emerged as innovative, non-formal educational strategies that encourage creative expression, emotional healing, and collaborative problem-solving, offering new avenues for youth involvement in peacebuilding. This study aims to evaluate the effectiveness of a participatory theater and arts program in enhancing youth empowerment and improving interpersonal conflict resolution skills in a post-conflict setting. A mixed-methods research design was implemented with 50 youth participants aged 15–22 from a post-conflict community. The intervention involved a twelve-week program combining drama workshops, storytelling circles, and collaborative performance creation. Quantitative data were collected through pre- and post-program assessments measuring empowerment indicators, self-confidence, and conflict resolution attitudes. Qualitative data were obtained through focus group discussions, reflective journals, and observation during rehearsals and performances. The findings indicate significant improvements in self-efficacy, communication competence, and constructive conflict-handling approaches among participants. Youth demonstrated enhanced empathy, reduced stigma toward rival groups, and greater willingness to engage in dialogue as solutions emerged collectively during arts-based exercises. Performances staged at community events successfully triggered intergroup interaction and re-opened public spaces for peaceful social exchange. The study concludes that participatory theater and arts provide a culturally adaptive and psychologically safe platform for youth to reconstruct identities, challenge narratives of division, and develop skills essential to long-term peacebuilding. Integrating arts-based empowerment programs into post-conflict community development may foster stronger social resilience and youth leadership in sustaining peace efforts.